Pengaruh Edukasi Kesehatan terhadap Pengetahuan Ibu dalam Pemberian Makanan Prelaktaeal - Hartati Bahar; Sartiah Yusran; Hariati Lestari; Sabrina Wahyuni Meyitia; Paridah Paridah (Jurnal Kendari Kesehatan Masyarakat, 2025)
Based on the 2019 Indonesian Health Profile, 67.74% of babies in Indonesia received exclusive breast milk, exceeding the target of 50%, while in Southeast Sulawesi Province, the figure reached 66.81%. Based on the 2023 Indonesian Health Survey, it was recorded that 28.2% of babies in Southeast Sulawesi aged 0-23 months received prelacteal food, with formula milk as the most common type (85.6%) and coconut water the least (0.3% ). This research uses a quantitative approach with a quasi-experimental design and purposive sampling technique. The total research sample was 25 respondents, namely mothers who have toddlers and live in the Lalodati Village area, Kendari City. The research method was carried out through lectures supported by poster media, with data collection using pre-test and post-test questionnaires. The research results showed an increase in the average level of maternal knowledge as measured through the pre-test and post-test. In the pre-test results, 13 respondents (52.0%) were in the sufficient category, while 12 respondents (48.0%) were in the poor category. Meanwhile, in the post-test results, 21 respondents (84.0%) were in the sufficient category, and 4 respondents (16.0%) were in the insufficient category. The t-test statistical test shows p-value (0.000) < (0.05), with an average pre-test score of 7.00 and post-test of 9.36. This shows that the education program was successful in increasing mothers' knowledge about prelacteal feeding